Importance Third Party Management Of Penitentiary Institutions: A Comparative Study Of Germany - Maryani, Desy (Jurnal Multidisiplin, 2024)
By conducting a comparative study, the importance of third-party management of correctional institutions (LPs), with a focus on the comparative practices implemented in Germany, can offer concrete, innovative and evidence-based solutions to overcome various challenges in the management of correctional institutions in Indonesia, while learning from the successes and challenges faced by developed countries such as Germany. Using qualitative research methods, this study analyses the policies and practices of prison management and their impact on prisoner rehabilitation. The research found that the third-party management model was able to improve operational efficiency, transparency, and the quality of rehabilitation programmes offered to prisoners. In addition, the results of the analysis show that the involvement of third parties in the management of prisons in Germany not only improves the living conditions of prisoners, but also contributes to the reduction of recidivism rates and the potential for implementing a similar model in Indonesia to overcome challenges in the correctional system, as well as providing policy recommendations that can support more effective and rehabilitation-oriented prison management.